Design of the Institute of Fine Arts and Design in Medan City With a Metaphor Architecture Approach - Syafira Oktaviani; Wahyuni Zahrah (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
The Institute of Fine Arts and Design is an art school that accommodates high levels of art study program enthusiasts in developing skills in the arts, producing creative and appreciative graduates. This study explores design aspects, such as function, site planning, design, and structure related to the art institute as a basis for design development analysis. The method used is a qualitative method through literature studies and field observations. Literature studies are used to analyze data related to the function of similar buildings and similar themes, namely metaphorical architecture. Field observations are conducted to observe and collect data related to the activities of the Fine Arts and Design Institute. The study concludes that in the design of fine arts and design institutes, creative design is needed through a metaphorical architecture approach. Metaphor architecture was raised as a theme because of the application of the principle of transferring information from one subject to another. The application of this concept is demonstrated by the form of the building mass series and the building facade with the play of secondary skin shapes.